CATHOLIC CHRISTIANITY IN INDIA - Mattam, Joseph (Asian Horizons, 2016)
The Catholic Church in India has a long history, beginning with the Apostle St Thomas. It is made up of three major Rites: the Syro Malabar, Syro Malankara and Latin. In the following pages, we shall survey briefly the rise of these three Rites in India, discuss the relation between them, and finally look at the overall picture of Catholic Christianity in India. The presence of the Church is not uniform in the whole country; the South has greater number of Catholics compared to other parts of India. In this paper I attempt to give a brief history of the growth of the Church in India, beginning with the St Thomas Christians of Kerala. After a brief history I attempt to show the contribution of Catholics to the country and the challenges faced by this community today. It is regrettable that the Dalits who had come over to the Christian community in order to free themselves from the caste oppression still continue to face discrimination in the Church, especially in the Southern regions. It is a challenging task for the Christians to become a true Church in India where people of various castes and other groups would feel welcome, respected and treated as equals.